2007
DOI: 10.1080/10495390600648741
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Differentiation of Dromedarian Camel of India

Abstract: Estimation of genetic variability and relationship among different livestock breeds is important for management of genetic resources for their sustainable utilization and conservation. This is more important when the livestock species, like camel, have shown a sharp decline in head count during the last decade. In the present study we estimated genetic variability and relationship among four camel breeds of India using 23 microsatellite loci. A total of 252 alleles were observed across all the four populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 16 publications
6
19
2
Order By: Relevance
“…Overall, the studied groups exhibited a moderate genetic differentiation of 5.2%, while the remaining 94.8% of the genetic variability was attributed to the differentiation within sub-populations (between individuals). This value was comparable to the genetic differentiation level previously reported (8.3%) for Tunisian camel population (Ould Ahmed et al, 2010), for Indian camel population (8.2%) (Vijh et al, 2007) and for Majorero camel in Canary Islands (3.1%) (Shulz et al, 2005). The within sub-population inbreeding estimate, per group across loci, were -0.369 (AT), -0.258 (AB) and -0.265 (ME).…”
Section: Resultssupporting
confidence: 90%
“…Overall, the studied groups exhibited a moderate genetic differentiation of 5.2%, while the remaining 94.8% of the genetic variability was attributed to the differentiation within sub-populations (between individuals). This value was comparable to the genetic differentiation level previously reported (8.3%) for Tunisian camel population (Ould Ahmed et al, 2010), for Indian camel population (8.2%) (Vijh et al, 2007) and for Majorero camel in Canary Islands (3.1%) (Shulz et al, 2005). The within sub-population inbreeding estimate, per group across loci, were -0.369 (AT), -0.258 (AB) and -0.265 (ME).…”
Section: Resultssupporting
confidence: 90%
“…It is evident from the above observation that Kachchhi and Mewari breeds have relatively less genetic variation as compared to the Bikaneri and Jaisalmeri, it is further substantiated by the fact that the Mewari is the least numerous and Kachchhi is the second least numerous breed of camel in India (Mehta et al 2011). The number of alleles and allele size range observed in the present investigation were broadly in agreement with the literature (Obreque et al 1998;Sasse et al 2000;Jianlin et al 2000;Vijh et al 2007;Spencer and Woolnough 2010;Banerjee et al 2012). Slight differences in the number of alleles and hence frequencies were expected due to the existence of actual genetic differences among the stocks used by different researchers.…”
Section: Discussionsupporting
confidence: 93%
“…The Kenyan and South African dromedaries have not been subjected to intensive selection (Mburu et al, 2003;Nolte et al, 2005); therefore this may be a possible reason for having a comparable MNA to ours. Analyses of 23 loci within 4 Indian dromedaries (Vijh et al, 2007) and 18 loci within 10 Chinese and Mongolian Bactrians (Xiaohong et al, 2012) yielded MNA values that were reasonably higher than ours.…”
Section: Discussioncontrasting
confidence: 47%
“…Polymorphic information content and H e estimates within current ecotypes were higher compared with Kenyan and United Arab Emirates (Mburu et al, 2003), Indian (Vijh et al, 2007), Tunisian (Ould Ahmed et al, 2010), Chinese, Mongolian (Xiaohong et al, 2012) and Saudi Arabian camels (Mahmoud et al, 2012(Mahmoud et al, , 2013. Nonetheless, study ecotypes showed lower H e values than Egyptian camel breeds (Karima et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation